Early cardiovascular prevention: the crucial role of nurse-led intervention - Anna Vittoria Mattioli; Sabina Gallina (BMC, 2023)
Abstract The present comment on Qiu's work intends to emphasize two points: (1) Cardiovascular prevention must start early due to the progressive nature of atherosclerosis. (2) growing evidence that coaching performed by nurses leads to effective results. Nurses can intercept the young population who must be sensitized and educated about prevention.